A review of thanatosis (death feigning) as an anti-predator behaviour - Humphreys, Rosalind K.; Ruxton, Graeme D. (Behavioral ecology and sociobiology, 2018)
Thanatosis—also known as death-feigning and, we argue more appropriately, tonic immobility (TI)—is an under-reported but fascinating anti-predator strategy adopted by diverse prey late on in the predation sequence, and frequently following physical contact by the predator. TI is thought to inhibit further attack by predators and reduce the perceived need of the predator to subdue prey further. The behaviour is probably present in more taxa than is currently described, but even within well-studied groups the precise taxonomic distribution is unclear for a number of practical and ethical reasons. Here we synthesise the key studies investigating the form, function, evolutionary and ecological costs and benefits of TI. This review also considers the potential evolutionary influence of certain predator types in the development of the strategy in prey, and the other non-defensive contexts in which TI has been suggested to occur. We believe that there is a need for TI to be better appreciated in the scientific literature and outline potentially profitable avenues for investigation. Future use of technology in the wild should yield useful developments for this field of study.